Different levels of energetic coupling between photosynthesis and respiration do not determine the occurrence of adaptive responses of Symbiodiniaceae to global warming. Issue 3 (21st July 2020) - Pierangelini, Mattia; Thiry, Marc; Cardol, Pierre
Summary: Disentangling the metabolic functioning of corals' endosymbionts (Symbiodiniaceae) is relevant to understanding the response of coral reefs to warming oceans. In this work, we first question whether there is an energetic coupling between photosynthesis and respiration in Symbiodiniaceae ( Symbiodinium, Durusdinium and Effrenium ), and second, how different levels of energetic coupling will affect their adaptive responses to global warming. Coupling between photosynthesis and respiration was established by determining the variation of metabolic rates during thermal response curves, and how inhibition of respiration affects photosynthesis. Adaptive (irreversible) responses were studied by exposing two Symbiodinium species with different levels of photosynthesis–respiration interaction to high temperature conditions (32°C) for 1 yr. We found that some Symbiodiniaceae have a high level of energetic coupling; that is, photosynthesis and respiration have the same temperature dependency, and photosynthesis is negatively affected when respiration is inhibited. Conversely, photosynthesis and respiration are not coupled in other species. In any case, prolonged exposure to high temperature caused adjustments in both photosynthesis and respiration, but these changes were fully reversible. We conclude that energetic coupling between photosynthesis and respiration exhibits wide variation amongst Symbiodiniaceae and does not determine the occurrence of adaptive responses in Symbiodiniaceae to temperature increase.